Embodiment and the New Shape of Black Theological Thought - Pinn, Anthony B. (Religion, Race, and Ethnicity, 2010)
Black theology tends to be a theology about no-body. Though one might assume that black and womanist theology have already given significant attention to the nature and meaning of black bodies as a theological issue, this inquiry has primarily taken the form of a focus on issues relating to liberation, treating the body in abstract terms rather than focusing on the experiencing of a material, fleshy reality. By focusing on the body as a physical entity and not just a metaphorical one, Pinn offers a new approach to theological thinking about race, gender, and sexuality.According to Pinn, the body is of profound theological importance. In this first text on black theology to take embodiment as its starting point and its goal, Pinn interrogates the traditional source materials for black theology, such as spirituals and slave narratives, seeking to link them to materials such as photography that highlight the theological importance of the body. Employing a multidisciplinary approach spanning from the sociology of the body and philosophy to anthropology and art history, Embodiment and the New Shape of Black Theological Thought pushes black theology to the next level